2011
DOI: 10.1097/pas.0b013e31821ec495
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Pit Dysplasia in Adjacent Gastric Mucosa in 414 Gastric Cancers

Abstract: Despite wide acceptance of the chronic gastritis-intestinal metaplasia-dysplasia-carcinoma sequence, especially for intestinal-type gastric adenocarcinoma, the precise nature of the subtle precursor lesions of gastric cancer remains to be delineated. For example, pit dysplasia with surface foveolar maturation is not well defined, nor is its prevalence and biological characteristics well characterized. We have evaluated the surrounding gastric mucosa of 414 gastric cancers for the presence of gastric pit dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
4
30
0
1
Order By: Relevance
“…Goblet cells may also be present. In this form of dysplasia, there is no surface epithelial involvement 18. In addition to these features, architectural abnormalities such as branching, budding, crowding and irregularly shaped glands are also identified.…”
Section: Rare Types Of Dysplasiamentioning
confidence: 98%
See 1 more Smart Citation
“…Goblet cells may also be present. In this form of dysplasia, there is no surface epithelial involvement 18. In addition to these features, architectural abnormalities such as branching, budding, crowding and irregularly shaped glands are also identified.…”
Section: Rare Types Of Dysplasiamentioning
confidence: 98%
“…These features are equivalent to low-grade and high-grade dysplasia without involvement of the surface epithelium. Pit dysplasia is found to be associated in 21% of the cases with intestinal-type gastric adenocarcinomas of the body/fundus with elevated morphology and immunoreactivity for MUC6 18. Pit dysplasia also shows p53 overexpression and increased Ki67 proliferation index 18…”
Section: Rare Types Of Dysplasiamentioning
confidence: 99%
“…However, subtle budding, branching, and crowding may be seen. 61,62 Pit dysplasia has been reported in association with older age, male sex, elevated morphology, and MUC6 expression. Importantly, these changes have been reported adjacent to bona fide neoplasia in 49%e72% of cases.…”
Section: Phenotype Based Risk Of Carcinomamentioning
confidence: 98%
“…Importantly, these changes have been reported adjacent to bona fide neoplasia in 49%e72% of cases. 62,63 Use of immunohistochemistry…”
Section: Phenotype Based Risk Of Carcinomamentioning
confidence: 99%
“…GED is defined according to its architectural and cytological abnormalities along the full length of the pit and the surface epithelium, and is categorized into adenomatous (or intestinal), foveolar (or gastric), and hybrid types based on its morphological characteristics [9-11]. However, several recent studies reported pit or crypt dysplasia, which exhibited dysplasia or atypical glandular or crypt lesions with surface maturation in Barrett esophagus [12,13] and the stomach [14-16]. With respect to the discrepancy that can occur between forceps biopsy and ER specimens, pit dysplasia (PD) might be diagnosed as GED in forceps biopsy and as a negative pathology after ER, and this could explain why NPD is sometimes found in ER specimens.…”
Section: Introductionmentioning
confidence: 99%